Społeczna odpowiedzialność biznesu jako źródło przewagi konkurencyjnej - Witek-Crabb, Anna (Corporate social responsibility as a source of competitive advantage, 2006)
The concept of corporate social responsibility, when implemented consistently may improve the company’s competitive position and help build the advantage over competitors. The most important benefits of running a responsible business are: improved image, savings, differentiation, higher morale of the workers and reduced risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 168-176